Norma canonica e illecito musicale. La musica come forma di disciplina delle masse nel diritto canonico latino (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. La constitutio “Docta sanctorum Patrum” - 3. La teoria dell’éthos - 4. Alla ricerca di una naturalis ratio - 5. Il cantus figuratus vel organicus alle soglie del XVI secolo - 6. Il Concilio di Trento - 7. Il De liberis recte instituendis (1533) del cardinale Jacopo Sadoleto - 8. Osservazioni conclusive.Canonical norm and musical offense. Music as a model of discipline of masses in Latin canon lawABSTRACT: This essay aims to examine the pedagogical value and repressive function of the liturgical music in classical canon law, with particular reference to the 14th century and to the Council of Trent. Some observations are dedicated to the Platonic matrix - that innervates both medieval and Renaissance thought - and to the concept of naturalis ratio.